The abnormal proplatelet formation in MYH9‐related macrothrombocytopenia results from an increased actomyosin contractility and is rescued by myosin IIA inhibition. (December 2013) - Chen, Y.; Boukour, S.; Milloud, R.; Favier, R.; Saposnik, B.; Schlegel, N.; Nurden, A.; Raslova, H.; Vainchenker, W.; Balland, M.; Nurden, P.; Debili, N.
Summary Background Mutations in the MYH9 gene cause autosomal dominant MYH9‐related diseases (MYH9‐RD) that associate macrothrombocytopenia with various other clinical conditions. The mechanisms giving rise to giant platelets remain poorly understood. Objectives/Patients To study the proplatelet formation (PPF) derived from megakaryocytes (MKs) generated in vitro from 11 patients with MYH9‐RD with different mutations, compared with controls. Methods Proplatelet formation from cultured patients' MKs was evaluated with or without blebbistatin or the ROCK inhibitor Y27632. Myosin IIA and actin distribution were studied in spreading MKs on different surfaces by immunoconfocal analysis. Kinetic studies of contractility were performed on spreading MKs and the impact of blebbistatin on the maturation of the patients' MKs was evaluated by electron microscopy. Results and Conclusions We show that in vitro MKs of 11 patients formed significantly fewer proplatelets than controls. MKs from MYH9‐RD displayed an abnormal spreading on polylysine, fibronectin and collagen, with a disorganized actin network and a marked increase in stress fiber formation. Traction force microscopy studies demonstrated an elevated level of contractile forces in adherent mutated MKs. The myosin II inhibitor blebbistatin and the ROCK inhibitor Y27632 both rescued the proplatelet formation defect and normalized the ultrastructural characteristics of MYH9‐RD MKs. Altogether, our results show that in MYH9‐RD, mutations modify the overall MYH9 function and provoke a proplatelet defect through an excess of actomyosin contractility in spreading MKs. These results may promote new therapeutic strategies aimed at reducing this actomyosin contractility.